Kinematic Analysis and Optimization of a Wheel Loader Mechanism - Segla, Stefan (Manufacturing Technology Journal, 2018)
The paper deals with kinematic analysis and dimensional optimization of a wheel loader mechanism. The kinematic analysis is based on the kinematic constraints of all joints in the mechanism. The objective function expresses the average angular displacement of the loader bucket and the optimization process leads to its minimum value. The wheel loader mechanism contains two hydraulic drives. The first drive is ensuring rotation of the boom (lifting the bucket) and the other rotation of the bucket. Optimization of the geometric dimensions of the wheel loader mechanism links gives their optimum values which ensure lifting the bucket with its negligible angular displacement carried out by just one hydraulic drive for rotation of the boom. The other hydraulic drive ensuring rotation of the bucket is stopped during lifting the bucket. The optimization results confirmed the possibility of lifting the bucket with just one hydraulic drive for rotation of the boom.
Keywords: wheel loader; mechanism; kinematic analysis; constraint; optimization